2021
DOI: 10.1213/xaa.0000000000001447
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Sequencing–Based Decision Support for Intensivists in Difficult-to-Diagnose Disease States: A Case Report of Invasive Cerebral Aspergillosis

Abstract: Aspergillus spp. are widespread environmental pathogens that can induce invasive aspergillosis, especially in immunocompromised patients. An 86-year-old female patient presented with a rare case of invasive cerebral aspergillosis. The aspergilloma invaded the intracranial region originating from the ethmoidal sinus and the orbital apex. In contrast to routine diagnostic procedures, next-generation sequencing (NGS) was able to identify the fungal pathogen in the cerebrospinal fluid as well as in plasma samples,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…In addition, we used commercially available next generation sequencing (NGS)‐based diagnostics for pathogen identification (Noscendo DISQVER®) that can detect bacteria, DNA viruses, fungi, and parasites in a single assay. 12 This highly sensitive assay also showed no evidence of a bacterial or fungal pathogen, so we are confident in diagnosing NBTE in our patient.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In addition, we used commercially available next generation sequencing (NGS)‐based diagnostics for pathogen identification (Noscendo DISQVER®) that can detect bacteria, DNA viruses, fungi, and parasites in a single assay. 12 This highly sensitive assay also showed no evidence of a bacterial or fungal pathogen, so we are confident in diagnosing NBTE in our patient.…”
Section: Discussionsupporting
confidence: 53%
“…All of our conventional blood cultures and blood culture‐negative endocarditis (BCNE)‐diagnostics (detecting Bartonella henselaeae, Coxiella burnetii, Mycoplasma pneumoniae, Legionella pneumophila, and Tropheryma whipplei) as well as beta‐D glucan remained negative. In addition, we used commercially available next generation sequencing (NGS)‐based diagnostics for pathogen identification (Noscendo DISQVER®) that can detect bacteria, DNA viruses, fungi, and parasites in a single assay 12 . This highly sensitive assay also showed no evidence of a bacterial or fungal pathogen, so we are confident in diagnosing NBTE in our patient.…”
Section: Discussionmentioning
confidence: 92%
“…These numbers reflect the diagnostic dilemma that IPA diagnosis clinicians face when treating critically ill patients. However, new diagnostic tools to better differentiate true infections from simple colonisations are on the horizon (e.g., next-generation sequencing (NGS) [39]), and might help to overcome this diagnostic dilemma.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the capacity of mNGS for viral detection in CSF remains poor ( 11–13 ). A few case studies describe NGS helping documenting infection by rare pathogens ( 9 , 12 , 14–16 ) but a large study on acute meningo-encephalitis showed disappointing results: only 22% of the infections were diagnosed by mNGS compared to 45% by conventional methods ( 13 ). In contrast, Hasan et al found good sensibility and specificity (100%; 95%, respectively) for a method designed to detect DNA pathogens only ( 11 ).…”
Section: Discussionmentioning
confidence: 99%